Measurement and Evaluation of E-service Quality Dimension on Customer Satisfaction and Brand Loyalty towards Online Travel Agency - Ahemed, Nahin; Dowpiset, Kitikorn; Chaipoopirutana, Sirion (Journal of Applied Economics and Management Strategy, 2018)
The continuous development of the Internet has facilitated businesses to enter into online web services. How businesses can utilize this growing business opportunity and can survive stiff competition is one of the important factors to be considered. Based on E-service quality dimensions, this study attempted to explore and examine the type of different services preferred by consumers of Agoda, a well-known online travel agency, it also further examined the relationship between customer satisfaction and loyalty. Based on the results, it could be observed that perceptions of service quality differed significantly on some demographic variables; e service quality dimensions had influence on customer satisfaction and customer loyalty; customer satisfaction and customer loyalty were positively related; and e-service quality was a significant predictor of customer satisfaction and customer loyalty. The empirical results about e-service quality dimensions were obtained for the online travel agency Agoda.